Meta-Analysis of Acupuncture Therapy for Blood Pressure Reduction in Pre-Elderly with Hypertension - Prabowo, Danang Aji; Prasetya, Hanung; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Blood pressure tends to increase with age. Hypertension or high blood pressure often occurs in pre-elderly individuals, who are aged between 45-59 years. Acupuncture is one of the therapies with mild side effects that can reduce blood pressure in pre-elderly individuals. This study aims to evaluate the effectiveness of acupuncture therapy in lowering blood pressure in pre-elderly individuals with hypertension based on similar previous research.Subjects and Methods: This study employed a systematic review and meta-analysis based on PICO framework: Population: Pre-elderly individuals with hypertension. Intervention: Acupunc-ture therapy. Comparison: Non-acupuncture therapy. Outcome: Blood pressure. Data were obtained from the PubMed, MEDLINE, Science Direct, BMC, and Google Scholar databases. The search process utilized keywords such as